The Role of Vitamins in Hemostasis - Quick, Armand J (Thrombosis and Haemostasis, 1975)
The physiological mechanism to prevent and control abnormal bleeding is dependent on three vitamins (C, K, and Q). Two of these are unequivocally established as essential for hemostasis while the existence of the third (Q) is supported by experimental evidence and by clinical and therapeutic observations (Quick 1972; Quick 1974). The interrelationship of these three vitamins has remained moot except for clue observations. Both vitamins C and K have a key structure in their molecules which supplies a redox mechanism, ascorbic acid and 2-methyl, 1,4-naphthoquinone, respectively. Both vitamins are concerned with growth. Lack of vitamin C, which clinically is the basic defect in scurvy, does not appear to cause a defect in blood coagulation while vitamin K affects the clotting mechanism by being essential for the production of four distinct clotting factors: prothrombin, factors VII, IX and X.In this presentation an attempt is made to correlate the action of the vitamin K-dependent clotting factors grouping them in a diagram to show how two systems of thrombin formation exist, one being essentially intrinsic, the second extrinsic requiring tissue thromboplastin and factor VII. The possible interlocking of vitamin Q in this mechanism is presented.